Evaluation of the ionic liquids for in-situ hydrolysis of lignocellulosic biomass by a locally-produced cellulase from Trichoderma reesei - Elgharbawy, Amal A.M.; Alam, Md. Zahangir; Jamal, Parveen; Kabbashi, Nassereldeen A; Moniruzzaman, Mohammed (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Utilization of the abundant raw materials in Malaysia as well as surmounting the obstacle of the shortcoming of fossil fuels resources are current concerns for the researchers. Development of the cellulase aims to enhance bioethanol production from lignocellulosic biomass such as empty fruit bunches (EFB) that resists hydrolysis due to the complex structure. Ionic liquids (ILs) have proved their ability to digest lignocellulose to be accessible by enzymes and thus it is expected to achieve a significant outcome by conducting both treatment and hydrolysis in one step by leaping cellulose recovery with anti-solvents. Palm kernel cake (PKC) was utilized as the primary media for cellulase enzyme production in solid-state bioconversion (SSB) by Trichoderma reesei. The PKC-cellulase (PKC-Cel) stability was assessed in several ionic liquids (ILs). For a duration of 6 hours, the PKC-Cel maintained significant levels of stability at the optimum conditions (50°C and pH 5.0). These findings could be a promising approach for bioethanol production considering that both enzyme and biomass are derived from agro-industrial waste